Inside Back Cover: SO2 Capture Using Porous Organic Cages (Angew. Chem. Int. Ed. 32/2021). Issue 32 (14th June 2021) - Martínez‐Ahumada, Eva; He, Donglin; Berryman, Victoria; López‐Olvera, Alfredo; Hernandez, Magali; Jancik, Vojtech; Martis, Vladimir; Vera, Marco A.; Lima, Enrique; Parker, Douglas J.; Cooper, Andrew I.; Ibarra, Ilich A.; et al.
Abstract : A functionalized porous organic cage (POC) demonstrating high SO2 capture capability and reversibility is reported by Andrew I. Cooper, Ilich A. Ibarra, Ming Liu, and co‐workers in their Research Article on page 17556 . The main source of SO2 emissions is the burning of fossil fuels, and alkaline scrubber‐based technologies are the main desulphurization methods in industry, which often cause corrosion of pipes and generate huge amounts of wastewater. With good processibility and proven scalability, POC materials offer a more sustainable option for SO2 capture.